2010
DOI: 10.1038/modpathol.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Detection of myxoid liposarcoma-associated FUS–DDIT3 rearrangement variants including a newly identified breakpoint using an optimized RT-PCR assay

Abstract: Myxoid/round cell liposarcoma is characterized by the recurrent translocations t(12;16)(q13;p11) and, less commonly, t(12;22)(q13;q12), which fuse FUS or EWSR1, respectively, to DDIT3 on chromosome 12. Although a number of different variant breakpoints have been described, greater than 90% of all cases have one of the three different FUS-DDIT3 fusions, which may have clinical significance. To identify the individual breakpoints, a sequence-specific assay such as reverse transcription-PCR (RT-PCR) is needed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…But MLS is distinguished from DFML by the lower extremities fascial planes predilection, the infiltration of surrounding structures, and the presence of lipoblasts on higher magnification [1,9]. Furthermore, molecular studies had shown that MLS was characterized by the recurrent translocations t(12;16)(q13;p11) and, less commonly, t(12;22)(q13;q12), which fuse FUS or EWSR1, respectively, to DDIT3 on chromosome 12 gene [10]. Narendra et al confirmed that FISH with DDIT 3 break-apart probe was a valuable adjunct in diagnosis or differential diagnosis of MLS [11].…”
Section: Discussionmentioning
confidence: 99%
“…But MLS is distinguished from DFML by the lower extremities fascial planes predilection, the infiltration of surrounding structures, and the presence of lipoblasts on higher magnification [1,9]. Furthermore, molecular studies had shown that MLS was characterized by the recurrent translocations t(12;16)(q13;p11) and, less commonly, t(12;22)(q13;q12), which fuse FUS or EWSR1, respectively, to DDIT3 on chromosome 12 gene [10]. Narendra et al confirmed that FISH with DDIT 3 break-apart probe was a valuable adjunct in diagnosis or differential diagnosis of MLS [11].…”
Section: Discussionmentioning
confidence: 99%
“…5 Myxoid liposarcoma represents 20-30% of all liposarcomas, mostly occurs in young adults, and is characterized by a translocation t(12;16)(q13;p11) or, in a few percent of the cases, a t(12;22)(q13;q12), leading to the chimeric fusion product FUS-DDIT3 or EWSR1-DDIT3, respectively. 25,26 According to the literature, one-third of myxoid liposarcoma patients develop distant metastases, 18,27,28 so effective systemic therapy is needed to improve the prognosis of many patients. Previous studies reported NY-ESO-1 expression in 95-100% of myxoid liposarcomas; these results were based on sample sizes ranging from 25 to 38 cases.…”
Section: Ny-eso-1 In Mesenchymal Tumorsmentioning
confidence: 99%
“…13;14 At least eleven different FUS-DDIT3 fusion types have been described and the fusion type does not impact clinical outcome. 2;13;15 Less than 5% of the cases harbour a t(12;22)(q13;q12) leading to an EWSR1-DDIT3 fusion, of which four different transcripts are described. 1;15;16 …”
Section: Introductionmentioning
confidence: 99%